MULTIPLE JEOPARDY: A RESEARCH REPORT ON INDIGENOUS FIRST-YEAR STUDENTS: WHAT IS KNOWLEDGE OR WHAT IS TRUTH? (Canadian Journal of Native Studies, 2026)
This study investigated the demographic and academic factorsassociated with academic progression of Indigenous first-yearstudents at the University of Manitoba. Student demographicsand measured academic factors were highly associated withdegree progression. First-year students who did not returnwere more likely to be male, at least 21 years of age, had notcompleted high school, and members of First Nations. Theseresults have implications for policy and student supports, anduniversities must work closely with Indigenous stakeholders toprepare and support Indigenous leaners, remove policy barriers,and address the need for changes to university culture andcurriculum.